2016
DOI: 10.1177/1541204016657395
|View full text |Cite
|
Sign up to set email alerts
|

Successes and Challenges in Recruiting and Retaining Gang Members in Longitudinal Research

Abstract: Members of hidden or hard-to-survey populations present challenges to social scientists seeking to engage them in empirical studies, especially if those efforts are longitudinal. In this article, we document the retention-related successes and failures of a longitudinal, social network-based study of active and desisting street gang members in Philadelphia, PA, and the District of Columbia. A purposive sample was used to identify and track 229 gang members at three points in time over 2 years to explore how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Instead, such knowledge is stored as artifacts in the boxes and hard drives of investigators, and even then, such information is only unearthed to revisit or extend substantive findings (Moule and Decker 2013; Sampson and Laub 1997). Even when a blueprint of study methods is provided (see, e.g., Arnold 2014; Eidson et al 2016), it is unclear which procedures or protocols are statistically more or less effective than other procedures. Moreover, much of what is known about how to track particular groups is known from the public health literature following substance abusers (Kleschinsky et al 2009; Walton, Ramanathan, and Reischl 1998), high-risk youth (McCuller et al 2002; Morrison et al 1997), and female sexual assault survivors (Ullman 2011).…”
Section: Longitudinal Research In Criminologymentioning
confidence: 99%
See 3 more Smart Citations
“…Instead, such knowledge is stored as artifacts in the boxes and hard drives of investigators, and even then, such information is only unearthed to revisit or extend substantive findings (Moule and Decker 2013; Sampson and Laub 1997). Even when a blueprint of study methods is provided (see, e.g., Arnold 2014; Eidson et al 2016), it is unclear which procedures or protocols are statistically more or less effective than other procedures. Moreover, much of what is known about how to track particular groups is known from the public health literature following substance abusers (Kleschinsky et al 2009; Walton, Ramanathan, and Reischl 1998), high-risk youth (McCuller et al 2002; Morrison et al 1997), and female sexual assault survivors (Ullman 2011).…”
Section: Longitudinal Research In Criminologymentioning
confidence: 99%
“…Gang membership may further exacerbate these issues. They may be more likely to perceive researchers (and outsiders in general) as untrustworthy and conceivably involved with law enforcement (Becker et al 2014; Curtis 2010; Eidson et al 2016). Despite these concerns, Mitchell et al (2018) found that gang members were just as likely as nongang members to participate in prison research and provide valid responses, standing in contrast to others who find that gang members are more secretive and harder to access by researchers (e.g., Fong and Buentello 1991; Pyrooz and Decker 2019).…”
Section: Longitudinal Research In Criminologymentioning
confidence: 99%
See 2 more Smart Citations
“…There is widespread agreement that early criminal initiation is a strong predictor of a long and prolific criminal career [7] (pp. [53][54], [8][9][10]. Thus, there is a high level of social (and academic) sensitivity to early symptoms of "social maladjustment", because such manifestations indicate a risk of amplifying adult crime rates in the future.…”
Section: Introductionmentioning
confidence: 99%